Assigning Punishment: Reader Responses to Crime News - Albrecht, Kat; Nadler, Janice (Frontiers in Psychology, 2022)
In this study we test how the composition of crime news articles contributes to reader perceptions of the moral blameworthiness of vehicular homicide offenders. After employing a rigorous process to develop realistic experimental vignettes about vehicular homicide in Minnesota, we deploy a survey to test differential assignments of blameworthiness operationalized as duration of suggested punishment. We find that readers respond to having very little information by choosing neutral or mid-point levels of punishment, but increase recommended punishment based on information about morally-charged conduct. By contrast, information about the perpetrator’s immigration status caused respondents to split into two groups on whether the offense deserves neutral or increased punishment. We find that political ideology strongly influences recommendations for more severe punishment when the immigration status of the perpetrator is revealed. We argue that this difference represents a moral dimension to punishment and blameworthiness that incorporates factors outside the active offense and therefore reveals the social influence of differential reporting in shaping public perception.